Innovative Learning Strategy Using H5P to Create Engaging Learning Modules for Students - Kurnianti, Apriliya; Isnanda, Reza Giga; Farkhani, Jodi Nur; Qodri, Krisna Nuresa (Universitas Muhammadiyah Yogyakarta, 2025)
Technology in education plays a crucial role in delivering effective learning, especially for students in Indonesian schools abroad. This study aims to develop and evaluate an interactive learning website based on WordPress and H5P, with a focus on Indonesian culture, particularly traditional dance. The website was developed locally using XAMPP and integrated with interactive videos, quizzes, and simulations. Evaluation results indicate that most students felt a greater connection to Indonesian culture, and the learning process became more engaging. This strategy has proven to enhance student engagement and strengthen national identity in multicultural environments